2012
DOI: 10.5194/acp-12-1229-2012
|View full text |Cite
|
Sign up to set email alerts
|

A simple relationship between cloud drop number concentration and precursor aerosol concentration for the regions of Earth's large marine stratocumulus decks

Abstract: Abstract. Aircraft-based measurements of cloud condensation nuclei (CCN), accumulation mode and Aitken mode number concentrations, cloud drop number concentration (CDNC), and selected ancillary measurements are presented for the three large, semi-permanent marine stratocumulus decks of the earth (in the Pacific offshore of California and Chile and in the Atlantic offshore of Namibia). Based on these data, a simple linear relationship between CDNC and the accumulation mode number concentration (AMNC) is derived… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 59 publications
(95 reference statements)
3
53
0
Order By: Relevance
“…3.2) showed that the number concentration of particles > 0.1 µm near shore was dominated by particles composed primarily of sulfate. These relatively large, soluble particles are efficient cloud condensation nuclei and explain the strong correlation between accumulation-mode aerosol concentration and droplet number concentration along 20 • S, which has also been observed in other stratocumulus regions (Twohy et al, 2005;Hegg et al, 2012).…”
Section: (A)mentioning
confidence: 91%
See 2 more Smart Citations
“…3.2) showed that the number concentration of particles > 0.1 µm near shore was dominated by particles composed primarily of sulfate. These relatively large, soluble particles are efficient cloud condensation nuclei and explain the strong correlation between accumulation-mode aerosol concentration and droplet number concentration along 20 • S, which has also been observed in other stratocumulus regions (Twohy et al, 2005;Hegg et al, 2012).…”
Section: (A)mentioning
confidence: 91%
“…This is similar to what other VOCALS researchers Allen et al, 2011) have used. Maximum droplet concentration was calculated using a 5-second pre-averaging technique for noise reduction as in Hegg et al (2012). A wing-mounted Particle Measuring Systems (PMS) Passive Cavity Aerosol Spectrometer Probe (PCASP-100) and a cabin mounted Ultra High Sensitivity Aerosol Spectrometer (UHSAS) counted and sized particles from 0.1-3.0 µm and 0.055-1.0 µm dry diameter, respectively.…”
Section: Methods and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coast of California is also important since in this area a persistent stratocumulus deck is found, which means that (1) aerosol retrieval from satellite is more challenging compared with more cloud-free areas, and (2) aerosol-cloud interaction is likely to be important (Hegg et al, 2012;Twohy et al, 2005).…”
Section: Study Domain and Experimental Designmentioning
confidence: 99%
“…Wettable particles with a dry diameter (D dry ) > 0.2 μm will activate at climatically relevant supersaturations (< 1%) almost regardless of their composition, while those containing highly soluble material may act as CCN with D dry as small as 0.05 μm [McFiggans et al, 2006;Andreae and Rosenfeld, 2008]. As such, the composition of aerosol particles, particularly those with D dry < 0.2 μm, can play an important role in determining the number concentration of subcloud CCN, which, combined with the dynamic nature of cloud supersaturation, is thought to ultimately determine the impact of aerosol particles on cloud drop size and number concentration [Hegg et al, 2012].…”
Section: Introductionmentioning
confidence: 99%